2016
DOI: 10.5812/traumamon.25091
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Dependency in Activities of Daily Living Following Limb Trauma in the Elderly

Abstract: Background: Traumatic injuries in the elderly often lead to permanent disabilities and long-term treatments that can adversely influence their activities of daily of living (ADL). The effect on ADL is an important outcome in elderly trauma. Objectives: The present study was designed to evaluate the predictive factors of dependency in ADL following limb trauma in elderly referred to Shahid Beheshti Hospital, Kashan, Iran, in 2013. Patients and Methods: This descriptive study was conducted on 200 traumatic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…In our study, age was the determinant factor for ADL activities such as bathing, dressing, toileting, continence and feeding. This finding was consistent with two previous studies that showed increasing dependence with age [ 20 , 54 ]. This may be due to the fact that elders usually have many health problems such as musculoskeletal disorders, visual and hearing impairment which deteriorated with age [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In our study, age was the determinant factor for ADL activities such as bathing, dressing, toileting, continence and feeding. This finding was consistent with two previous studies that showed increasing dependence with age [ 20 , 54 ]. This may be due to the fact that elders usually have many health problems such as musculoskeletal disorders, visual and hearing impairment which deteriorated with age [ 55 ].…”
Section: Discussionsupporting
confidence: 94%
“…This study focuses on ADL-related assessments among subjects aged 50 years and above and the evaluations are based on the three main phases after a fracture i.e., pre-fracture phase, ward admission phase and the post-discharge phase (3 months after hospital discharge). In this study, the four variables (age, gender, fracture type and ability to walk before fracture) were chosen in accordance with several previous studies that these variables contribute much influence on ADL [ 20 , 25 , 26 , 27 ]. Thus, this study was performed focusing on the Asian population, particularly in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations